Preclinical assessment of a tissue-engineered vasomotive human small-calibered vessel based on a decellularized xenogenic matrix: histological and functional characterization - Heine, Jörg; Schmiedl, Andreas; Cebotari, Serghei; Mertsching, Heike; Karck, Matthias; Haverich, Axel; Kallenbach, Klaus (Tissue engineering, 2011)
Objectives: Tissue-engineered arterial vessels (TEAV) offer substantial advantages in small-calibered human-bypass-grafting and vascularized scaffold applications. However, histological composition of TEAV must allow for functional properties, such as vasomotoricity. Aim of this study was to characterize human TEAVs regarding morphology and vasomotoricity. - - Methods: Three groups containing segments of porcine carotid artery <5 mm in diameter (native [NA, n = 6], decellularized [DA, n = 6], and decellularized/reseeded in a bioreactor [RA, n = 7] with human vascular endothelial [hvECs] and smooth muscle cells [hvSMCs]) were examined. Light and scanning electron microscopy were applied, and hvSMCs- and hvECs-associated Vasomotoricity Test conducted in Krebs-solution was used for characterization of revitalized TEAVs. - - Results: Morphologic examination showed cell-free extracellular matrix in DAs. Light microscopy demonstrated intact extracellular matrix components in circle-layered formation in cross sections of DAs. RAs showed small cells migrating along the remaining medial fiber structures and flat cell layers at the luminal site, identified as hvECs and hvSMCs with lower CD-31 and α-actin signaling than controls. Scanning electron microscopy showed intact flat cell layers on luminal surfaces of RAs and dense hvSMCs at their media site. DAs showed decreasing strain after stimulation. RAs retrieved vasomotoricity compared to DAs, but showed reduced contraction and incomplete relaxation compared to NAs. - - Conclusions: This study shows that revitalization of DA with human vascular cells resembles NA-like morphology and can ensure vasomotoricity of TEAVs.